Hubungan Tingkat Kecemasan dengan Angka Kejadian Nokturia pada Mahasiswa/i Fakultas Teknologi Pertanian Universitas Brawijaya selama Pandemi COVID-19 - Pradyaputri, Naura Shafa; Daryanto, Besut; Sagita, Zendy (Jurnal Klinik dan Riset Kesehatan, 2024)
Background: Nocturia is the most common and disturbing symptom in lower urinary tract disorders. Younger people, particularly college students, are more affected by nocturia, which can have a negative impact on their academic performance. A study revealed that anxiety often occurs simultaneously with nocturia and has a reciprocal association. Aim: The purpose of this study is to examine the frequency of nocturia in agricultural technology students during the COVID-19 pandemic and the association between anxiety levels and nocturia incidence. Methods: Analytic observational study with cross sectional design. The Google form questionnaire contains questions about student characteristics data, the ICIQ-N questionnaire contains the frequency of nocturia and disturbance scores, and the ZSAS questionnaire for anxiety levels. Data analyzed used Chi Square test to analyze the relationship between anxiety level and nocturia. Results: The results showed that there was an insignificant relationship between anxiety levels (p=0.307). Nocturia is a symptom that is often experienced by students. The disturbing score increases along with the severity of nocturia. Conclusion: There was a weak association between anxiety level and nocturia.